Interim report on an investigation on mechanised information retrieval service in a specialised subject area - Cleverdon, Cyril W.; Harding, P. (Cranfield Institute of Technology, 1970)
The report covers the work undertaken in establishing and operating for a period of six months an S.D.I. service in the field of precision engineering. The performance and costs of the system are given and the problems which would be involved in a commercial operation are considered. The view is taken that it would be difficult for a system of this type to be economically viable in the short term.